Nahwu dan Shorof Sebagai Ilmu Pengetahuan Perspektif Ontologi dalam Ranah Filsafat (Pusat Riset dan Inovasi Nasional, 2026)
This study is entitled Nahwu and Shorof as Sciences in the Ontological Perspective within the Realm of Philosophy. The purpose of this research is to examine the essence of nahwu and shorof not merely as technical tools for understanding the Arabic language, but also as scientific entities that possess ontological dimensions in philosophy. Nahwu is understood as the science that regulates the arrangement of words within sentences, while shorof functions to form and transform words according to specific patterns. From an ontological perspective, both are not simply linguistic instruments, but rather representations of the structure and form of linguistic reality that reflect the orderliness of human thought. The analysis demonstrates that nahwu and shorof play a fundamental role in preserving the integrity of meaning in Arabic texts, while also serving as a means to comprehend the essence of language as a living and dynamic entity. Thus, nahwu and shorof can be regarded not only as practical sciences in language learning, but also as philosophical disciplines within the ontology of knowledge, revealing the essence of form and structure of language in relation to human and societal reality.